The Making of Sri Lanka’s Post-Conflict Economic Package and the Failure of the 2001-2004 Peace Process. - Venugopal, R (CRISE (Department of International Development, University of Oxford), 2009)
This paper explores the role of domestic actors and the international donor community in the evolution of Sri Lanka’s post-conflict economic package of 2001-2004. It argues that the inappropriateness of this economic package was a critical element that contributed to the overall failure of the peace process. Due to the heavy influence of corporate interest groups and international donors, the peace agenda, and the country’s post-conflict PRSP, was effectively tethered to an aggressive programme of market reforms. Although the government felt that the market reform agenda would spur rapid economic growth and buy support for the peace process, it ended up doing the very reverse. Consequently, the relatively narrow constituency of opposition to the peace process swelled in size and benefited from the support gained from those who opposed the government’s economic policies. The market-reform laden economic agenda enjoyed very narrow social support and indeed, generated considerable opposition and hostility. In addition, the government’s simultaneous pursuit of fiscal austerity to secure desperately needed concessionary financing from the IMF meant that not only was there very little in the way of a peace dividend to distribute, there were instead cutbacks on subsidies and employment opportunities that disproportionately affected the rural Sinhalese poor. The inherent unpopularity of this economic agenda was compounded by the absence of broad consultation in its formulation, despite the fact that this was required as part of the PRSP process.